Dynamic Phosphorylation of the SARS-CoV-2 Nucleocapsid Protein Regulates Viral Particle Assembly - Yu, Yanying; Wang, Ziqiao; Yu, Kuai; Liu, Kunpeng; Huyan, Yangnan; Sun, Bo; Ju, Xiaohui; Yao, Qiaorui; Xie, Yifei; Shan, Chao; Zhang, Rong; Zhao, Jincun; et al. (LangTaoSha Preprint Server, 2026)
The SARS-CoV-2 nucleocapsid (N) protein plays critical roles in viral genome replication and virion assembly. Although the N protein is extensively phosphorylated within its central Ser/Arg-rich region by glycogen synthase kinase-3 (GSK-3), the functional significance and dynamic regulation of its phosphorylation state during the viral life cycle remain incompletely understood. Here, we show that N phosphorylation is essential for productive SARS-CoV-2 infection. Mechanistically, phosphorylation was dispensable for viral RNA replication, but was required for the interaction of N with the viral nonstructural protein 3 (nsp3), a double-membrane vesicle (DMV)-associated protein involved in nascent viral RNA export. This interaction promoted the recruitment of N to DMVs for viral RNA packaging. In contrast, mature virions predominantly contained dephosphorylated N, indicating that N undergoes a phosphorylation-to-dephosphorylation transition during virion morphogenesis. Consistently, dephosphorylated N preferentially interacted with the viral membrane (M) protein and accumulated in the ERGIC, the site of virion assembly, suggesting that N dephosphorylation promotes the transition from DMV-associated RNA packaging to ERGIC-associated virion assembly. We further identified protein phosphatase 1 (PP1) as the principal host phosphatase that directly catalyzes N dephosphorylation. Genetic depletion or pharmacological inhibition of PP1 markedly impaired both SARS-CoV-2 trVLP and authentic SARS-CoV-2 infection. Mechanistically, PP1 recognized N through a conserved RVxF motif within the N-terminal region of N, and disruption of this interaction abolished efficient N dephosphorylation and severely compromised viral infection. Together, our findings define a phosphorylation-dephosphorylation switch that coordinates distinct functions of the SARS-CoV-2 N protein during infection and identify the PP1-N axis as a potential antiviral target.
Keywords: SARS-CoV-2; nucleocapsid protein; phosphorylation; viral assembly; protein phosphatase 1